Building Memory Representations for Exemplar-Based Judgment: A Role for Ventral Precuneus - Stillesjö, Sara; Nyberg, Lars; Wirebring, Linnea Karlsson (Frontiers in Human Neuroscience, 2019)
The brain networks underlying human multiple-cue judgment, the judgment of a continuous criterion based on multiple cues, have been examined in a few recent studies, and the ventral precuneus has been found to be a key region. Specifically, activation differences in ventral precuneus (as measured with functional magnetic resonance imaging, fMRI) has been linked to an exemplar-based judgment process, where judgments are based on memory for previous similar cases. What aspects of exemplar-based judgment ventral precuneus supports is however poorly understood. Ventral precuneus is a brain region important for various episodic memory processes, where increased engagement of this region together with the ventromedial prefrontal cortex (vmPFC) and the medial temporal lobes (MTL) during learning have been linked to retrieval success. Several alternatives are plausible, for example that reduced brain activity in ventral precuneus during learning to make exemplar-based judgments could reflect reduced needs for visuo-spatial attention as a function of learning to master the task. The present study used fMRI during a multiple-cue judgment task to gain novel neurocognitive evidence informative for the link between learning-related activity changes in ventral precuneus and exemplar-based judgment. Participants (N = 27) spontaneously learned to make judgments during fMRI, in a multiple-cue judgment task specifically designed to induce exemplar-based processing. Contrasting brain activity during late learning to early learning indeed revealed higher activity in ventral precuneus, the bilateral MTL and the vmPFC. Activity in the ventral precuneus and the vmPFC was found to parametrically increase between each judgment event, and activity levels in the ventral precuneus predicted performance after learning. These results are interpreted such that the ventral precuneus supports the aspects of exemplar-based processes that are related to episodic memory, tentatively by building and retrieving memory representations for judgment.